Influence of polymorphisms in TNF-α and IL1β on susceptibility to alcohol induced liver diseases and therapeutic potential of miR-124-3p impeding TNF-α/IL1β mediated multi-cellular signaling in liver microenvironment - Dasgupta, Debanjali; Ghosh, Suchandrima; Dey, Indrashish; Majumdar, Swagata; Chowdhury, Saheli; Das, Subhas; Banerjee, Sanjana; Saha, Mehelana; Ghosh, Amit; Roy, Neelanjana; Manna, Alak; Ray, Sukanta; et al. (Frontiers in Immunology, 2023)
Background and aims Alcoholic liver disease (ALD) is the leading cause of the liver cirrhosis related death worldwide. Excessive alcohol consumption resulting enhanced gut permeability which trigger sensitization of inflammatory cells to bacterial endotoxins and induces secretion of cytokines, chemokines leading to activation of stellate cells, neutrophil infiltration and hepatocyte injury followed by steatohepatitis, fibrosis and cirrhosis. But all chronic alcoholics are not susceptible to ALD. This study investigated the causes of differential immune responses among ALD patients and alcoholic controls (ALC) to identify genetic risk factors and assessed the therapeutic potential of a microRNA, miR-124-3p. Materials and methods Bio-Plex Pro™ Human Chemokine analysis/qRT-PCR array was used for identification of deregulated immune genes. Sequencing/luciferase assay/ELISA detected and confirmed the polymorphisms. THP1 co-cultured with HepG2/LX2/HUVEC and apoptosis assay/qRT-PCR/neutrophil migration assay were employed as required. Results The combined data analysis of the GSE143318/Bio-Plex Pro™ Human Chemokine array and qRT-PCR array revealed that six genes (TNFα/IL1β/IL8/MCP1/IL6/TGFβ) were commonly overexpressed in both serum/liver tissue of ALD-patients compared to ALC. The promoter sequence analysis of these 6 genes among ALD (n=322)/ALC (n=168) samples revealed that only two SNPs, rs361525(G/A) at -238 in TNF-α/rs1143627(C/T) at -31 in IL1β were independently associated with ALD respectively. To evaluate the functional implication of these SNPs on ALD development, the serum level of TNF-α/IL1β was verified and observed significantly higher in ALD patients with risk genotypes TNF-α-238GA/IL1β-31CT+TT than TNF-α-238GG/IL1β-31CC. The TNF-α/IL1β promoter Luciferase-reporter assays showed significantly elevated level of luciferase activities with risk genotypes -238AA/-31TT than -238GG/-31CC respectively. Furthermore, treatment of conditioned medium of TNF-α/IL1β over-expressed THP1 cells to HepG2/LX2/HUVEC cells independently showed enhanced level of ER stress and apoptosis in HepG2/increased TGFβ and collagen-I production by LX2/huge neutrophil infiltration through endothelial layer. However, restoration of miR-124-3p in THP1 attenuated such inter-cellular communications and hepatocyte damage/collagen production/neutrophil infiltration were prohibited. Target analysis/luciferase-reporter assays revealed that both TNF-α/IL1β were inhibited by miR-124-3p along with multiple genes from TLR4 signaling/apoptosis/fibrogenesis pathways including MYD88, TRAF3/TRADD, Caspase8/PDGFRA, TGFβR2/MCP1, and ICAM1 respectively. Conclusion Thus, rs361525(G/A) in TNF-α and rs1143627(C/T) in IL1β gene may be used as early predictors of ALD susceptibility among East Indian population. Impeding overexpressed TNF-α/IL1β and various genes from associated immune response pathways, miR-124-3p exhibits robust therapeutic potential for ALD patients.